The Use of European Culinary Heritage for the Organization of Leisure (Laisvalaikio tyrimai, 2018)
Sustainable farming and ecological culinary heritage and food production along with balanced strategy and technologies could be closely related. This would make conditions for healthy food production. Research object was European culinary heritage leisure organization. Research aim was reveal opportunities for organizing leisure time activities with European culinary heritage. Research methods were research literature review and questionnaire survey. Research results revealed that the majority of respondents equated the concept of free time with a good rest tasting and enjoying traditional regional culinary dishes. Regional culinary heritage is one of the best possibilities to promote traditional regional food as well as to help you spend your leisure time purposefully.Keywords: leisure, culinary heritage dishes, European Culinary Heritage network.